Risk Analysis of Occupational Safety and Health (K3) Using the HIRADC Method on Chiller Replacement Works: A Case Study - Toni Yuri Prastowo; Rahmadika Luthfi Manaf Imsarif; Dedy Sanjaya; Nana Taryana (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2024)
Occupational safety and health (K3) is an important aspect that must be considered in construction projects to prevent work accidents. This study aims to analyze potential risks and determine control measures using the Hazard Identification Risk Assessment and Determining Control (HIRADC) method on a chiller replacement work at a hotel renovation project in Jakarta, Indonesia. Potential hazards were identified through direct observation, worker interviews, and document review. Risk assessment was carried out by calculating the likelihood and severity scores to determine risk levels. Several control measures were implemented based on the risk hierarchy. A risk comparison before and after implementing controls showed a reduction in risk levels. Structural analysis using ETABS proved that the temporary reinforcement provided structural safety. The estimated cost of Rp. 250,456,350 met K3 budget provisions. This study demonstrates that risk analysis using HIRADC is effective in reducing risks and ensuring K3 aspects in construction works.